Business marketing management B2B - Hutt, Michael D.; Speh, Thomas W. (South-Western Cengage Learning, 2013)
The new edition includes additional emphasis on automated B2B practices and the impact of the Internet. A well-balanced mix of cases equips students with a variety of hands-on applications. With its complete and timely treatment of business marketing, BUSINESS MARKETING MANAGEMENT minimizes the overlap with other marketing courses.